2015
DOI: 10.1309/ajcpuxlp7xd8oqyy
|View full text |Cite
|
Sign up to set email alerts
|

The LAST Guidelines in Clinical Practice

Abstract: Implementation of the p16 LAST guidelines resulted in a significant increase in p16 use and a significant increase in the positive predictive value of p16+ HSIL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Three staining patterns were recorded: absent, heterogeneous and block (Figure S1). Block expression was distinguished from heterogeneous staining by using the recommendation for p16 interpretation from LAST 4; that is, block expression is characterized by diffuse staining of tumor cells in nuclear and/or cytoplasmic compartment with at least moderate intensity with virtually no negative tumor cell clusters. Interobserver reproducibility between two observers (PR and MK) was assessed for a subset of 120 cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three staining patterns were recorded: absent, heterogeneous and block (Figure S1). Block expression was distinguished from heterogeneous staining by using the recommendation for p16 interpretation from LAST 4; that is, block expression is characterized by diffuse staining of tumor cells in nuclear and/or cytoplasmic compartment with at least moderate intensity with virtually no negative tumor cell clusters. Interobserver reproducibility between two observers (PR and MK) was assessed for a subset of 120 cases.…”
Section: Methodsmentioning
confidence: 99%
“…Normal cells express variable amounts of p16 protein that can be detected by immunohistochemistry (IHC) in both nuclear and cytoplasmic localizations (heterogeneous p16 expression pattern) 3. There are two abnormal p16 expression patterns: absent and overexpressed, the latter also referred to as block expression as recommended by the Lower Anogenital Squamous Terminology Standardization Project for HPV‐Associated Lesions (LAST) 4. In keeping with its role as a tumor suppressor, absence of p16 expression can occur due to various mechanisms including homozygous deletion, loss of function mutations, promoter hypermethylation and translational suppression 5.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study have found that the reproducibility of H&E staining morphological diagnoses by pathologists is poor and that the consistency of CIN2 diagnosis is <50%. 14 The reproducibility of CIN2+ morphological diagnosis in the ASCUS/LSIL Triage Study for Cervical Cancer (ALTS) was only 43%. 15 In another study, two pathologists agreed with 84% and 81%, respectively, for CIN3 diagnosis; for CIN2, the agreement was 13% and 31%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…diagnosis is < 50%. 12 The reproducibility of CIN2 + morphological diagnosis in the ASCUS/LSIL Triage Study for Cervical Cancer (ALTS) was only 43%. 13 In another study, two pathologists agreed with 84%…”
Section: Comparison Of Detection Methods For Cervical Precancerous Lementioning
confidence: 99%